2010
DOI: 10.1097/aog.0b013e3181d56cc5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Myogenic Stem Cells on Contractile Properties of the Repaired and Unrepaired Transected External Anal Sphincter in an Animal Model

Abstract: In this animal model, injection of myogenic stem cells at the time of external anal sphincter repair resulted in enhanced contractile function at 90 days compared with repair alone. Without repair, function of the external anal sphincter was not improved by stem cell therapy at any time point. These results suggest that addition of myogenic stem cells improves both acute and long-term function of the external anal sphincter after mechanical injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 28 publications
0
47
0
Order By: Relevance
“…Previous functional anal sphincter assessments have mostly been performed in vitro using anal sphincter muscle samples from euthanized animals to measure the contractility after electrical stimulation 10, 12, 17, 37. Salcedo et al measured in vivo function of the anal sphincter after a sphincterotomy or pudendal nerve crush followed by either rat bone‐marrow derived MSC injection or saline 18.…”
Section: Discussionmentioning
confidence: 99%
“…Previous functional anal sphincter assessments have mostly been performed in vitro using anal sphincter muscle samples from euthanized animals to measure the contractility after electrical stimulation 10, 12, 17, 37. Salcedo et al measured in vivo function of the anal sphincter after a sphincterotomy or pudendal nerve crush followed by either rat bone‐marrow derived MSC injection or saline 18.…”
Section: Discussionmentioning
confidence: 99%
“…Several animal studies have been reported on anal sphincter dysfunction induced by surgical techniques (18)(19)(20)(21)(22)(23). For instance, Salcedo, et al (20) investigated two different models of anal sphincter dysfunction (i.e., sphincterotomy and bilateral pudendal nerve transection) in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…However, these 7 7 studies were based on the hypotheses that these models had complete fecal incontinence. Since then, several conventional anal dysfunction animal models were reported, such as the sphincterotomy model (19)(20)(21)(22), cryoinjured anal sphincter model (23) and pudendal nerve transection model (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…This enabled achievement of histologically proven destruction of one sector of the anal sphincter, provoking a significant decrease in contractile force. We preferred this approach to sphincterotomy (1,12,19,35), since it is not only more convenient to perform but also less traumatic for the rat.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, among the few experimental studies of myoblast anal sphincter injection, this is the first report of a longitudinal functional study in individual animals (12,13,35). To achieve myoblast tracking, injected cells were transduced with a GFP-encoding lentiviral vector.…”
Section: Myoblast Cell Therapy In Fecal Incontinencementioning
confidence: 99%